Female-Specific Labor Regulation and Employment: Historical Evidence from the United States - Joanne Haddad; Lamis Kattan (CESifo GmbH, 2024)
By the end of the nineteenth century, labor legislation for women had become a prominent issue in the United States, with most states enacting at least one female-specific work regulation. We examine the impact of three previously unexplored legislation: seating, health and safety, and night-work regulations. Given that not all states adopted these laws, and the staggered nature of adoption, we rely on a difference-in-differences strategy design to estimate the effects on female gainful employment. Our findings indicate that laws regulating health and safety conditions and restricting women's night work increased the likelihood of female employment by about 4% to 8%, accounting for about 10% to 20% from the total increase during our period of analysis. Examining heterogeneous effects reveals that younger and married women without children witnessed the largest increase in the likelihood of employment. We also document that native, higher-class and literate women were also incentivized to join the workforce. Women's labor supply in the decades under consideration has been estimated to be quite inelastic with respect to own wage. Nevertheless, we find sizable labor force participation responses to the female-specific labor regulation we study. This indicates that the legislation must have shifted women's labor supply curves, either because it made jobs more pleasant, or because it improved perceptions about how respectable it is for a woman to work in the labor market. Both channels would reduce disutility from work, and increase labor supply at any given wage level. Our findings hold important implications for policymakers and advocates seeking to promote gender equality in the labor market.
Keywords: J08; J16; J21; J24; J78; K31; 330; labor supply; labor law; gender law; gender norms